Presence of circulating Her2-reactive CD8 + T-cells is associated with lower frequencies of myeloid-derived suppressor cells and regulatory T cells, and better survival in older breast cancer patients - Bailur, Jithendra Kini; Gueckel, Brigitte; Derhovanessian, Evelyna; Pawelec, Graham (Breast cancer research : BCR, 2015)
Introduction Breast cancer is one of the most common cancers among women. Its incidence is increasing in many countries and a higher number of older women are now being diagnosed with the disease. Immune parameters are implicated in disease progression, and the frequencies of both myeloid-derived suppressor cells (MDSCs) and regulatory T cells (Tregs), associated with tumour burden, have been suggested to be indicators of poor prognosis in cases of metastatic breast cancer. Methods Here, we have assessed the frequency of peripheral Tregs and MDSCs in relation to in vitro T cell responses to Her2 antigen in 40 untreated breast cancer patients 65 to 87 years of age at diagnosis. Results The five-year survival rate of patients who mounted a CD8+ T cell response to Her2 peptides and had a lower frequency of Lin − CD14 + HLA-DR − MDSCs was 100% compared to only 38% in patients without Her2-reactive CD8+ T cells and with higher frequencies of MDSCs ( P = 0.03). Patients who lacked a CD8 response to Her2 tended to have higher frequencies of MDSCs. Similarly, patients who lacked a CD8 response to Her2 and had higher frequencies of CD4 + Foxp3 + CD127 low CD25 + Tregs had only 50% survival compared to the 100% survival of patients who did mount a CD8 response and had lower frequencies of Tregs ( P = 0.03). A similar trend was observed for activated (CD4 + CD45RA − Foxp3 hi ) but not resting Tregs (CD4 + CD45RA + FoxP3 + ). This survival advantage was observed in both metastatic and non-metastatic patients. Conclusions Our data demonstrate a negative role of both MDSCs and Tregs in the prognosis of breast cancer patients, the mechanism of which might be through dampening favourable CD8+ T cell immune responses to tumour-associated antigens.